Patient decision support resources inform decisions about cancer susceptibility genetic testing and risk management: a systematic review of patient impact and experience - Kohut, Kelly; Morton, Kate; Turner, Lesley; Shepherd, Jonathan; Fenerty, Vicky; Woods, Lois; Grimmett, Chloe; Eccles, Diana M.; Foster, Claire (Frontiers in Health Services, 2023)
Abstract Background: People Patients with a genetic cancer susceptibility are presented with complex management options involving difficult decisions, for example about genetic testing, treatment, screening and risk-reducing surgery/medications. This review sought to explore the experience of patients using decision support resources in this context, and the impact on decision-making outcomes. Methods: Systematic review of quantitative, qualitative and mixed-methods studies involving adults with or without cancer who used a decision support resource pre- or post-genetic test for any cancer susceptibility. To gather a broad view of existing resources and gaps for development, digital or paper-based patient resources were included and not limited to decision aids. Narrative synthesis was used to summarise patient impact and experience. Results: Thirty-six publications describing 27 resources were included. Heterogeneity of resources and outcome measurements highlighted the multiple modes of resource delivery and personal tailoring acceptable to and valued by patients. Impact on cognitive, emotional, and behavioural outcomes was mixed, but mainly positive. Findings suggested clear potential for quality patient-facing resources to be complement genetic counselling and support decision-makingacceptable and useful. Conclusions: Decision support resources about genetic cancer susceptibility are likely useful to support decision-making, but need should to be co-designed with patients according to evidence-based frameworks and allow personal tailoring for culture and preferences. More research is needed to study impact and outcomes, particularly in terms of longer term follow-up to identify whether people patients follow through on decisions and whether any increased distress is transient. Innovative, streamlined resources for pre-diagnostic genetic test education are needed to scale up delivery of genetic cancer susceptibility testing for people patients with cancer in mainstream oncology clinics. Tailored patient-facing decision aids should also be made available to people patients identified as carriers of once they have been found to carry a pathogenic gene variant causing increasedthat increases future cancer risks, to complement traditional genetic counselling and shared decision-making with health care professionals.